Doctoral Studies in the Area of Didactics of Chemistry in the Czech Republic — Development and the Current State - Čtrnáctová, Hana; Klečková, Marta (Scientia in educatione, 2013)
The contribution concerns the development of the subject of chemistry education with respect to its institutionalization during scientific preparation and doctoral studies. It characterizes these forms of studies, their importance and the results obtained. The first part of the contribution concerns the scientific preparation in the subject: The theory of chemistry teaching which has existed here since 1970s. In the second part of the contribution, we’ll deal with the meaning of doctoral studies for the development of the subject of chemistry education and the characteristics of quantitative and qualitative measures of the doctoral studies programme: Education in Chemistry and Didactics of Chemistry in the Czech Republic. These studies were accredited at the Charles University — Faculty of Science in 2003, and at Palacky University — Faculty of Science in 2007. In the contribution, we show the main parameters and demands of this study, the aim of doctoral dissertations since 2004, and their contributions for the further development of the subject.